Effects of Ethrel Application and Packaging on Mango Fruit Quality - E. Elkashif, Mohamed; M. Elamin, Osman; B. Mohamed, Tawheda (Gezira Journal of Agricultural Science; Vol 1 No 1 (2003), 2021)
Experiments were conducted at the National Institute for the Promotion  of Horticultural Exports, University of Gezira, Wad  Medani, Sudan, during May 1997 and 1998 to investigate the effects of Ethrel and polyethylene packaging on mango fruit quality. Mango fruit quality, Mango fruits were  harvested at the mature-green stage and treated with Ethrel or  left as control. Fruits were packed in either intact or perforated polyetlhylene packages or left unpacked. The experiments were set up in a completely randomized design with three replications. Ethrel treatment accelerated  the rate of fruit ripening as shown by an increase in total soluble solids, yellowing and a decrease in fruit firmness and starch content Fruits packed in intact polyethylene packages resulted in the  lowest weight loss, followed by those packed in perforated films, whereas unpacked fruits showed the highest weight loss and lowest quality manifested in shriveling and deterioration